Faculty Senate, Agenda, April 16, 2009 - Faculty Senate, Valdosta State University (Valdosta, Ga: Valdosta State University Archives and Special Collections, 2009)
Valdosta State University. Faculty Senate, Agenda, April 16, 2009
1 electronic document. Faculty Senate, Agenda, April 16, 2009. 7 pages.
Keywords: Valdosta State University. Faculty Senate; Corporation reports; Committees; Electronic records